Anti-disturbance GITSMC with quick reaching law for speed control of PMSM drive - Salah Eddine Halledj; Amar Bouafassa (Bulletin of Electrical Engineering and Informatics, 2022)
In this article, in order to minimize response time and enhance anti-disturbance performance of parmanent magnet synchronous motor, a global integral terminal sliding mode control based on improved quick reaching law (GITSMC-QRL) is developed. This novel reaching law has two terms which play a key role of bringing state trajectory to sliding surface as quick as possible whenever the system is close to or far from the manifold. The proposed controller cannot only speed up the convergence rate, but also has ability to suppress the chattering and ensure finite time stability. In order to avoid the chattering phenomenon caused by load disturbances and high switching gain of sliding mode control, an extended hyperbolic tangent state observer is designed as feedforward compensation compensator that is added to GITSMC. Finally, the novel scheme is validated on paremanent magnet synchronous motor (PMSM) drive through simulation, and the comparative results in various conditions show the robustness, the feasibility and the effectiveness of the proposed controller.